Nilai Sipakainge dalam Kearifan Lokal Bugis: Strategi Ekonomi Islam untuk Pelestarian Wisata Bahari Parepare - Hasmawati; Cahyani, Indah; Natalia, Lisa (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the value of Sipakainge in Bugis local wisdom as a strategy for marine tourism conservation in Parepare City through an Islamic economics approach. Sipakainge, which means mutual reminding of goodness and social responsibility, is a moral value that plays a crucial role in maintaining harmony between humans and the environment. The declining cleanliness and conservation in Parepare's marine tourism areas, such as Paputo Beach, Mattirotasi, and Lumpue, indicate the need for a management approach based on cultural and Islamic values. This research employs a qualitative method with observation, interview, and documentation techniques involving coastal communities, tourism managers, and traditional leaders. The findings reveal that the internalization of the Sipakainge value can build collective community awareness in preserving the marine and coastal environment as an implementation of the maslahah (public benefit) principle in Islamic economics. Furthermore, collaboration between the government, community, and tourism businesses based on the Sipakainge value can create sustainable, religious, and socially equitable marine tourism management. Thus, the integration of local wisdom and Islamic economic values forms a strategic foundation for maintaining the sustainability of Parepare's marine tourism while enhancing the welfare of the coastal community.